The fate of a key Arctic copepod in future ocean acidification: Integrating molecular, organismal, and evolutionary thinking in the face of climate change - Bailey, Allison Michelle (UiT The Arctic University of Norway, 2017)
The papers I, II and III of this thesis are not available in Munin. Paper I: Bailey, A., Thor, P., Browman, H. I., Fields, D. M., Runge, J., Vermont, A., Bjelland, R., Thompson, C., Shema, S., Durif, C. M. F., Hop, H.: “Early life stages of the Arctic copepod Calanus glacialis are unaffected by increased seawater pCO2”. Available in ICES Journal of Marine Science 2016. Paper II: Bailey, A., De Wit, P., Thor, P., Browman, H. I., Bjelland, R., Shema, S., Fields, D. M., Runge, J. A., Thompson, C., Hop, H.: “Regulation of gene expression underlies tolerance of the Arctic copepod Calanus glacialis to CO2-acidified seawater”. (Manuscript). Paper IV: Thor, P., Bailey, A., Dupont, S., Calosi, P., Søreide, J., De Wit, P., Guscelli, E., Loubet-Sartrou, L., Deichmann, I., Candee, M., Svensen, C., King, A. L., Bellerby, R. G.J.: “Potential for rescue from future ocean acidification by extant physiological differences among distinct Arctic copepod populations”. (Manuscript). Uptake of anthropogenic carbon dioxide (CO2) into the world’s oceans is increasing seawater acidity in a process termed ocean acidification. This is predicted to have harmful effects on a variety of marine organisms. With the greatest and fastest changes in pH expected to occur the Arctic seas over the next 100 years, the need for understanding the effects of low pH on Arctic marine organisms is pressing. This thesis examines the effects of projected levels of ocean acidification on the physiology of a key component of the Arctic marine ecosystem, the copepod Calanus glacialis, using molecular, organismal, and evolutionary methodologies to investigate the effects of low pH throughout its lifespan, in combination with other stressors (food availability) and across geographically distant sub-populations (to predict their capacity for adaptation or acclimation in the future). Young stages of the copepod, potentially the most sensitive, were tolerant to realistic pH levels for future ocean acidification: the nauplii developed successfully from egg to ...